WHERE IS VICTORIAN ECOCRITICISM?. Issue 4 (5th August 2015) - Taylor, Jesse Oak
Abstract : The most striking thing about reviewing the field of Victorian ecocriticism is that there is so little of it. This relative absence is all the more perplexing given that ecocritical work on Romanticism and nineteenth-century American literature is so profuse. Thoreau and Wordsworth remain the most-discussed authors in a field that was in many respects inaugurated by Jonathan Bate's Romantic Ecology: Wordsworth and the Environmental Tradition (1991) and Lawrence Buell's The Environmental Imagination: Thoreau, Nature Writing and the Formation of American Culture (1995). Romanticism remains the point of departure for some of the most influential studies in the field, including those like Timothy Morton's Ecology Without Nature (2009) that challenge many of its core precepts. Meanwhile, ecocriticism has expanded to include many other periods and regions, with collections ranging from The Ecocritical Shakespeare (2011) to Postcolonial Ecologies (2011), and unsurprisingly, a strong turn toward the contemporary.